An apple cyclic nucleotide-gated ion channel gene highly responsive to Botryosphaeria dothidea infection enhances the susceptibility of Nicotiana benthamiana to bacterial and fungal pathogens. (April 2018) - Zhang, Weiwei; Dong, Chaohua; Zhang, Yugang; Zhu, Jun; Dai, Hongyi; Bai, Suhua
Highlights: An apple CNGC was first reported to be involved in plant defense against diseases. Overexpression of MdCNGC1 conferred susceptibility on N. benthamiana to pathogens. MdCNGC1 overexpression affects the induction of ROS and SA by pathogen infection. Overexpression of MdCNGC1 reduced induced expression of PRs and callose deposition. Abstract: Apple ring rot caused by the fungus Botryosphaeria dothidea is one of the devastating diseases. Up to date, the responsive mechanism of apple plant to this disease remains unclear. In the present study, an apple CNGC gene (designated as MdCNGC1 ) was found among highly expressed genes responding to B. dothidea infection. The expression of MdCNGC1 was different among apple cultivars with different resistance to B. dothidea . Intriguingly, MdCNGC1 expression was not induced by other two apple pathogens, Marssonina coronaria and Valsa ceratosperma . Ectopic overexpression of MdCNGC1 in Nicotiana benthamiana conferred elevated susceptibility to bacterial and fungal pathogens. Notably, overexpression of MdCNGC1 reduced salicylic acid (SA) accumulation induced by Alternaria alternata or Pseudomonas syringae . Decreased induction of pathogenesis-related ( PR ) genes and ROS accumulation were also observed in MdCNGC1 -overexpressing plants. Up-regulated scavenging systems as indicated by enhanced expressions of CAT, APX, SOD genes and activities of antioxidative enzymes may in part contribute to reduced ROS accumulation. MdCNGC1 expression in N. benthamiana also decreased flg22 and chitosan-induced callose deposition and lowered the expression of NbPMR4, an ortholog of Arabidopsis callose synthase gene PMR4 . These combined results suggested that MdCNGC1 might be a negative factor to plant resistance to bacterial and fungal pathogens.